Coulson & Richardson's chemical engineering, J.M. Coulson and J.F. Richardson : solutions to the problems in Chemical engineering, volume 2 (5th edition) and volume 3 (3rd edition) - Backhurst, J. R. (Butterworth-Heinemann, 2002)
Richardson et al provide the student of chemical engineering with full worked solutions to the problems posed in Chemical Engineering Volume 2 "Particle Technology and Separation Processes" 5th Edition, and Chemical Engineering Volume 3 "Chemical and Biochemical Reactors & Process Control" 3rd Edition. Whilst the main volumes contains illustrative worked examples throughout the text, this book contains answers to the more challenging questions posed at the end of each chapter of the main texts. These questions are of both a standard and non-standard nature, and so will prove to be of interest to both academic staff teaching courses in this area and to the keen student. Chemical engineers in industry who are looking for a standard solution to a real-life problem will also find the book of considerable interest. * Contains fully worked solutions to the problems posed in Chemical Engineering Volumes 2 and 3 * Enables the reader to get the maximum benefit from using Volumes 2 and 3 * An extremely effective method of learning.